Fighting in the city in the military thought of the Workers’ and Peasants’ Red Army (1918–1946) - Czernielewski, Konrad Aleksander (City and War, 2021)
The author of the paper presented the views of theoreticians and commanders of the Workers’ and Peasants’ Red Army (WPRA) for city fighting and conquering, since the uprising Red Army in February 1918 until the end of World War II. He discussed how the senior officers of the Red Army viewed the issue of the specificity of combat in an urbanized area – which is nowadays referred to as the black tactic. He also presented the problem – always important for commanders of both infantry, armored weapons, artillery and aviation – whether to capture cities from the front or rather encircle – forcing the enemy to withdraw his forces. The author discussed it mainly on the basis of the battles in Stalingrad and Berlin. The battles in the latter city are called the Berlin Strategic Offensive Operation in the Soviet historiography. He also described the circumstances of the attack on Bobruisk during Operation Bagration. In the latter case, a dispute arose between Joseph Stalin, who was a supporter of a massive attack on this city, and Konstanty Rokossowski, who insisted on concentrically attacking along both banks of the Berezina. Interestingly, in this dispute, the Generalissimo finally agreed with K. Rokossowski. The author also presented the unsuccessful attempt to capture Kołobrzeg from the 45th Armored Brigade of the Guard of Col. Mikołaj Morgunow from the composition of the 1st Panzer Army of General Col. Mikhail Katukov and the successful campaign to capture Częstochowa from the march. The paper presents the views of the most important Soviet commanders of the Second World War: Grigory Zhukov, Konstanty Rokossowski, Ivan Koniev, Ivan Bagramian, Vasily Chukov, Grigory Nadysiew, and the German ones: Erich von Mannstein and Heinz Guderian.